Religion, hypermobility and digital media in global Asia: faith, flows and fellowship - Yoe, Tan Meng (Media, culture and communication in migrant societies, 2020)
Digital media is changing the ways in which religion is practiced, understood, proselytised and countered. Religious institutions and leaders use digital media to engage with their congregations who now are not confined to single locations and physical structures. The faithful are part of online communities which allow them a space to worship and to find fellowship. Migrant and mobile subjects thus are able to be connected to their faith - whether home grown or emerging - wherever they may be; thus providing them with an anchor in unfamiliar physical and cultural surroundings. As Asia rises, mobilities associated with Asian populations have escalated. The notion of 'Global Asia' is a reflection of this increased mobility, where Asia includes not only Asian countries as sites of political independence, but also the transnational networks of Asian trans/migrants, and the diasporic settlements of Asian peoples all over the world. This collection features cutting edge research by scholars across disciplines seeking to understand the role and significance of religion among transnational mobile subjects in this age of digital media, and in particular, as experienced in Global Asia